Portrait of a Priestess: Women and Ritual in Ancient Greece - Connelly, Joan Breton (Princeton University Press, 2022)
Frontmatter -- Contents -- Acknowledgments -- Abbreviations -- Chapter 1 Introduction: Time, Space, Source Material, and Methods -- Chapter 2 Paths to Priesthood: Preparation, Requirements, and Acquisition -- Chapter 3 Priesthoods of Prominence: Athena Polias at Athens, Demeter and Kore at Eleusis, Hera at Argos, and Apollo at Delphi -- Chapter 4 Dressing the Part: Costume, Attribute, and Mimesis -- Chapter 5 The Priestess in the Sanctuary: Implements, Portraits, and Patronage -- Chapter 6 The Priestess in Action: Procession, Sacrifice, and Benefaction -- Chapter 7 Priestly Privilege: Perquisites, Honors, and Authority -- Chapter 8 Death of the Priestess: Grave Monuments, Epitaphs, and Public Burial -- Chapter 9 The End of the Line: The Coming of Christianitys -- Chapter 10 Conclusions -- Notes -- Bibliography -- Index of Monuments -- Index of Inscriptions -- Index of Priestesses -- General Index -- Glossary -- Maps -- Plates